The jobless future : sci-tech and the dogma of work - Aronowitz, Stanley (University of Minnesota Press, 1994)
This widely reviewed and highly successful book examines the job market of tomorrow. Aronowitz and DiFazio take you behind the headlines to challenge the idea that a high-tech economy will provide high-paying jobs for all who want them. Instead, they demonstrate that we're more likely to see continued layoffs and job displacement.